SISTEM INFORMASI MANAJEMEN TOKO PERIKANAN IMA - Ratri Isnaini; Riki Afriansyah; Ahmat Josi (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
Toko Perikanan IMA is a shop that is engaged in the sale of fishing equipment in Sungailiat city. To manage store data such as sales data and product stock, Toko Perikanan IMA still uses a manual check by making written in the administration book which makes the owner get difficult. In fact, by managing store data, the owner can choose and make the right decisions. Besides that, marketing and promotion in Toko Perikanan IMA are very restricted and doesn't optimal. Therefore, a management information system is needed to solve the problem of the owner shop. Honestly, with a management information system, can more expect to make it easier for owner shop to manage a store data, both sales data, product data, product stock data, etc. Besides that, is be able to present information about fisheries that is more up to date and can promote the store widely without space and time-limited. The method used in building this system is the waterfall method. This method is used so that the system can be structured and neatly organized. To make a system design the owner uses UML (Unified Modeling Language) and the programming languages used are PHP and MySQL.